PERSEPSI PENGUNJUNG DAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN EKOWISATA AIR TERJUN AEK MARTUA DI KABUPATEN ROKAN HULU - Rahlem, Dedek; Yoza, Defri; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Rokan Hulu has one of the natural famous tourism namely Aek Martua Waterfalls, Aek Martua waterfalls managed by local goverment who cooperate with the local society. Management of the Aek Martua waterfalls that  managed by local society will affect the level of visitors, because the visitors has own assessment of there tourism attractions. The purpose of this research is to determine participation society in management waterfalls. This research held in Aek Martua waterfalls and Bangun Purba Rokan Hulu, Riau Province. In August until September 2016. The type of this research is descriptive research with qualitative approachment. Based on research results perception of the visitors about ecotourism in Aek Martua waterfalls many as 93,3% visitors know the conditions of Aek Martua waterfalls, through the affective aspect as many as 76,7% said that Aek Martua waterfalls is still beautiful and 96,7% agree to contribute. There are 60% of society participated in discussion and give opinion for the plan of the tourist attraction, role of society forward implementation as much as 90% participated to managed Aek Martua waterfalls. For receive benefits 46,7% society accept economics benefit, and as many as 36,7% society  contributed in monitoring and evaluating activities Aek Martua waterfall.Keywords: Ecotourism, Aek Martua, Perception visitors, Participation of Society